Radiação UV- precipitação- lignina e seus efeitos na decomposição da liteira em clareiras na Amazônia Central - Florentino, Ana Paula Pires (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
Litter decomposition is essential for carbon and nutrients cycling. This process is determined by abiotic (temperature and precipitation) and biotic factors (litter chemistry and biota decomposing activity). Recent studies have shown the effects of UV radiation on litter photodegradation and biota decomposing photoinhibition in arid and semi-arid ecosystem. This study aimed to investigate the interactions of UV radiation with precipitation and litter chemistry effects on organic matter decomposition in a tropical rainforest. Therefore, a decomposition experiment was conducted with leaves of the two species (Eschweilera coriacea and Micrandropsis scleroxylon) with contrasting lignin under differents UV radiation and precipitation. The experiment was conducted in ten gaps with approximately 100 m2 in a central Amazon terra-firme forest. Among the factors evaluated, precipitation was the main driver of litter decomposition. The difference of dry mass remaining litter in lower lignin content was independent of UV radiation. However, for the litter in higher lignin content was find interaction between precipitation and UV exposure. Although, only at lower lignin litter content, differences in litter remaining dry mass was find modification in the organic composition. However provisional, these results suggest the potential impact of UV radiation on the dynamics of organic matter and the carbon cycle in central Amazon gap areas.
Keywords: Ciclo do carbono; Fotodegradação; Biodegradação; Clareiras; Florestas tropicais